TEN YEARS OF JURNAL AKUNTANSI DAN KEUANGAN INDONESIA: A BIBLIOMETRIC STUDY - Firmansyah, Irman (UI Scholars Hub, 2021)
This study aims to map articles in the Jurnal Akuntansi dan Keuangan Indonesia (JAKI) published by the Faculty of Economics and Business, Universitas Indonesia, for ten years (2011 to 2020). This study deployed a bibliometric analysis as an investigative method. The data were analyzed with R biblioshiny analytical framework. The findings revealed that JAKI was considerably consistent in publishing articles every period. JAKI publishes six articles each number and two publication numbers annually. In particular, there were 120 articles gained from 2011 to 2020. Based on the analysed articles, the most frequently emerging word from unigrams was ‘study’ and ‘earnings management’ from bigrams. Additionally, the most popular topics during those years (2011 to 2020) were 'income', 'risk', 'slack', 'foreign', and 'direct.’ Moreover, the most closely related words to other words encompassed ‘study’, ‘result’, and ‘research.’ Further, the words ‘study', 'result', and 'effect' represented a strong density and centrality of words. Therefore, they should be cultivated.